3D printed microstructured Au/TiO2 catalyst for hydrogen photoproduction. (September 2019) - Elkoro, Ander; Soler, Lluís; Llorca, Jordi; Casanova, Ignasi
Graphical abstract: Highlights: A fabrication method of Au/TiO2 monoliths by 3D printing has been developed. The H2 photoproduction rates of post-impregnated samples performed best–. The diameter of the TiO2 microfilaments was a key design parameter for H2 production. Abstract: We successfully 3D printed Au/TiO2 monoliths for photogenerating hydrogen from water/ethanol gaseous mixtures under dynamic conditions. Monolith designs were printed by additive superposition of microfilaments of titania-based pastes. Factors influencing the efficiency of the photocatalytic reactions, including impregnation of gold nanoparticles (Au NPs), calcination temperature, diameter of microfilaments and monolith design, are investigated. The use of preformed Au NPs assured a constant Au particle size (ca. 4 nm) for all samples, which allowed to a precise assessment of the effect of the design of 3D-printed titania monoliths on photocatalytic activity. The impregnation of preformed Au NPs before or after the 3D printing process has a strong influence on the photocatalytic efficiency. The pre-impregnated monoliths have a homogeneous Au NPs distribution throughout the microfilaments, whereas the post-impregnated ones present an asymmetric distribution of Au NPs, observing a high gold concentration at the surface and lower gold concentrations in the inner regions of the printed microfilaments. The gold concentration of the Au-loading suspension was reduced ca. 10 times in post-impregnated samples to ensure a similar amount of Au NPs anchored at the surface of the microfilaments, according to an XPS analysis of the pre- and post-impregnated samples. Although the photocatalytic performance of the pre-impregnated monoliths was improved when samples were calcined at 400 °C, due to a stronger contact between the Au NPs and the microfilament supports, the post-impregnated samples with 100 times lower Au concentration (0.005 wt.%) exhibited enhanced catalytic performances. Under similar geometric open section and photon absorption conditions, the photoproduction of hydrogen on a weight (or volume) basis increased strongly as the diameter of the filaments decreased, which is explained by a progressive increase of the surface-to-weight and surface-to-volume ratios. The best photoactivity was obtained with a post-impregnated titania monolith 3D printed with microfilaments with 200 μm in diameter, which yielded 0.24 mol H2 min −1 gAu −1 .